Hubungan Faktor Sosial Ekonomi dengan Kejadian Prolapsus Uteri di RSUD Dr. Moewardi - Putra, Ivan Aristo Suprapto; Darto, .; Subandono, Jarot (Nexus Kedokteran Klinik, 2013)
Background: Socioeconomic factors in Indonesian citizen was different on every person. Especially on work, many variants of works would cause on variants of workload. On the other side, work varied effect on different income. Earnings would affect on the food consumed. Low collagen contained food intake could affect the low level of collagen. Risk factors for uterine prolapse was higher workload, higher parity and lower collagen level. Methods: This research was an analytic obervational with case control design. Sampling technique was fixed disease sampling for the case group and random sampling for the control group. The research was conducted by interviewing a sample directly in the  obstetric clinic  Dr. Moewardi hospital The sample was 36 person, divided into 18 samples of group cases and 18 control group samples. Dependent variable was the incidence of uterine prolapse and independent variables were socioeconomic factor. Data were analyzed by chi-square test then followed by multivariate analyse  logistic regression. Results: Distribution characteristics of uterine prolapse by age most results were in the age of 40-49 (16.67%). Based on the results, the highest number of children was 4 children (16.7%). The test results with regression analysis showed significance between socioeconomic factors to the incidence of uterine prolapse. Workload had p = 0.017 and OR = 0.186, p = 0.039 whereas income., and OR = 7.208, 95% confidence interval. Nagelke R square of 38.2%. Conclusions: Socio economic factor include workload and income significantly affected incidence of uterine prolapse. Keywords: Socio-economic factors, workload, income, uterine prolapse